Respon Santri Terhadap Kesenian Hadrah Di Pondok Pesantren Ad-Dawami Pasir Kawung Kabupaten Bandung - Damyati, Ahmad (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2013)
This research aims to determine the response of santri (Islamic students) to the art of hadrah; to understand the implementation of hadrah art as a medium of da'wah (Islamic preaching); and to determine the response of santri to hadrah art as a medium of da'wah at the Ad-Dawami Islamic Boarding School in Pasir Kawung, Bandung Regency. The theory used is the S-O-R theory with a quantitative research method. There are 3 research findings. First, the students responded well to the hadrah art form available at the Ad-Dawami Islamic boarding school in Pasir Kawung, Bandung Regency. Second, the implementation of hadrah art as a medium of da'wah at the Ad-Dawami Islamic boarding school is very significant. Third, the students' response is of significant value, with 81% of them responding positively to hadrah art as a medium of da'wah at the Ad-Dawami Islamic boarding school in Pasir Kawung, Bandung Regency.